Comparative population genomics dissects the genetic basis of seven domestication traits in jujube. (1st June 2020) - Guo, Mingxin; Zhang, Zhongren; Cheng, Yanwei; Li, Sunan; Shao, Peiyin; Yu, Qiang; Wang, Junjie; Xu, Gan; Zhang, Xiaotian; Liu, Jiajia; Hou, Linlin; Liu, Hanxiao; et al.
Abstract: Jujube ( Ziziphus jujuba Mill.) is an important perennial fruit tree with a range of interesting horticultural traits. It was domesticated from wild jujube ( Ziziphus acidojujuba ), but the genomic variation dynamics and genetic changes underlying its horticultural traits during domestication are poorly understood. Here, we report a comprehensive genome variation map based on the resequencing of 350 accessions, including wild, semi-wild and cultivated jujube plants, at a >15× depth. Using the combination of a genome-wide association study (GWAS) and selective sweep analysis, we identified several candidate genes potentially involved in regulating seven domestication traits in jujube. For fruit shape and kernel shape, we integrated the GWAS approach with transcriptome profiling data, expression analysis and the transgenic validation of a candidate gene to identify a causal gene, ZjFS3, which encodes an ethylene-responsive transcription factor. Similarly, we identified a candidate gene for bearing-shoot length and the number of leaves per bearing shoot and two candidate genes for the seed-setting rate using GWAS. In the selective sweep analysis, we also discovered several putative genes for the presence of prickles on bearing shoots and the postharvest shelf life of fleshy fruits. This study outlines the genetic basis of jujube domestication and evolution and provides a rich genomic resource for mining other horticulturally important genes in jujube.